Study of Physicochemical Properties of Commercial Drinking Bottled Water Brands - Jatoi, A. R.; Jakhrani, A. Q.; Mukwana, K. C.; Laghari, A. N.; Tunio, M. M. (Engineering, Technology & Applied Science Research, 2018)
Drinking water quality is being affected by industrial effluents, pesticides and fertilizers, poor sanitation services and unhygienic practices. Thus, upper and middle-class people used to prefer bottled water for drinking instead of tap water. Increasing demand for bottled water leads to the presence of low quality branded waters in the market due to the high demand and improper quality checks. In this regard, this study is carried out to assess the physicochemical properties of various branded bottled waters. For that, ten different water brand samples, coded from S1 to S10, were collected from Safoora Goth, Karachi. Various physicochemical quality parameters of branded water samples were analyzed according to the set procedures of American Society for Testing and Materials. It was discovered that the pH levels of S9 and S8 bottled water brands were slightly less than World Health Organization guideline values. The physical and chemical quality parameters of S1, S2, S4, S5, S7, and S10 branded bottled water samples were found within standards.